The role of non-protein-coding RNAs in ischemic acute kidney injury - Sabet Sarvestani, Fatemeh; Afshari, Afsoon; Azarpira, Negar (Frontiers in Immunology, 2024)
Acute kidney injury (AKI) is a condition characterized by a rapid decline in kidney function within a span of 48 hours. It is influenced by various factors including inflammation, oxidative stress, excessive calcium levels within cells, activation of the renin-angiotensin system, and dysfunction in microcirculation. Ischemia-reperfusion injury (IRI) is recognized as a major cause of AKI; however, the precise mechanisms behind this process are not yet fully understood and effective treatments are still needed. To enhance the accuracy of diagnosing AKI during its early stages, the utilization of innovative markers is crucial. Numerous studies suggest that certain noncoding RNAs (ncRNAs), such as long noncoding RNAs (lncRNAs), microRNAs (miRNAs), and circular RNAs (circRNAs), play a central role in regulating gene expression and protein synthesis. These ncRNAs are closely associated with the development and recovery of AKI and have been detected in both kidney tissue and bodily fluids. Furthermore, specific ncRNAs may serve as diagnostic markers and potential targets for therapeutic interventions in AKI. This review aims to summarize the functional roles and changes observed in noncoding RNAs during ischemic AKI, as well as explore their therapeutic potential.